The skeletal muscle microbiopsy method in exercise and sports science research: A narrative and methodological review - Newmire, D. E.; Willoughby, D. S. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Background The skeletal muscle microbiopsy protocol was introduced to the Exercise and Sports Science (ESS) research field in 1999 and has been used as a protocol to directly examine muscular structural and biochemical changes. There is much variation in the reporting of the microbiopsy protocol and its related pre- and post-procedure for participant care and sample collection. The purpose of this narrative and methodological review is to compare the microbiopsy to the traditional Bergström protocol used in the ESS field, identify and summarize all related microbiopsy protocols used in previous ESS studies and determine the most frequently used microbiopsy protocols aspects and associated pre- and post-biopsy procedures.